2022
DOI: 10.1021/acs.jafc.2c04129
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Quercetin to Hemoglobin Reduced Hemin Release and Lipid Oxidation

Abstract: The interactions between quercetin and bovine (or human) hemoglobin (Hb) were systematically investigated by fluorescence, UV−vis absorption spectroscopy, and molecular docking to demonstrate the structural mechanism by which quercetin affected the Hb redox state and stability. Quercetin could interact with the central cavity of the Hb molecule with one binding site to generate an Hb−quercetin complex, and the hydrophobic interaction played an important role in the formation of the complex. The binding constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Similar studies have been reported by Tian et al. (2022). In addition to the stability enhancement mechanisms, molecular docking can be utilized to explore the mechanisms of undesirable food molecular interactions.…”
Section: Applications Of Molecular Simulation To Food Protein–ligand ...supporting
confidence: 91%
“…Similar studies have been reported by Tian et al. (2022). In addition to the stability enhancement mechanisms, molecular docking can be utilized to explore the mechanisms of undesirable food molecular interactions.…”
Section: Applications Of Molecular Simulation To Food Protein–ligand ...supporting
confidence: 91%
“…With the extension of storage time, Mb is oxidized, the structure of globin is opened, the connection between heme and globin is weakened (Wu et al, 2017). Mb continues to be oxidized to form NHI (Tian et al, 2022). The contents of total iron and NHI in KR muscle were the lowest (P < 0.05).…”
Section: Changes In Cattle Total Iron Hi and Nhi Contents In Differen...mentioning
confidence: 99%
“…The structural changes at position 3 can lead to a significant increase in the antioxidant activity of quercetin, which enables it to better remove free radicals generated during protein glycation. The reducing power of rutin for hydroxyl radicals at the same concentration was only about 52% that of quercetin based on Tian et al’s study . Furthermore, it has been reported that quercetin has a higher affinity for amyloid polypeptide, inhibiting fibrillation more effectively in pancreatic cells compared to rutin .…”
Section: Resultsmentioning
confidence: 95%